OPTIMALISASI PENDAMPINGAN SENAM HIPERTENSI UPAYA PENCEGAHAN KENAIKAN TEKANAN DARAH PASIEN HIPERTENSI WILAYAH KERJA PUSKESMAS KRATONAN KOTA SURAKARTA - Noorratri, Erika Dewi; Ardhiani, Nurul Devi; Sari, Irma Mustika (PPM STIKES Adi Husada, 2024)
Introduction & Aim: Hypertension is a very dangerous non-communicable disease. This is because hypertension sufferers do not find any typical symptoms as a warning, this is what is usually called the silent killer. There are several treatments used to reduce blood pressure in hypertension sufferers, one of which is hypertension exercise. Hypertension exercise is one of the sports and one of the therapies used for hypertension sufferers, which is a non-pharmacological therapy. The aim of this service is that residents can independently practice hypertension exercises. Method of Activity: namely measuring blood pressure and hypertension exercises carried out in March 2024 with a total of 12 people in approximately 2 hours. Blood pressure is measured in hypertensive patients before and after carrying out hypertension exercises Results: There was an average change in blood pressure of 4.27% in systole and 6.32% in diastole in hypertensive patients in the working area of ​​the Kratonan Health Center, Surakarta City. Discussion: Elderly people experienced a decrease in blood pressure after doing hypertension exercises. Hypertension exercise is one method used to prevent an increase in blood pressure. This method is a non-pharmacological treatment. Hypertension exercises can be done easily using SOPs or existing methods. Hypertension exercises are easy to do and don't require a lot of money.